Epidemiology and outcomes of children with accidental hypothermia: A propensity-matched study. Issue 2 (February 2017) - Totapally, Abhinav; Leoncio, Michael; Beltramo, Fernando; Meyer, Keith; Raszynski, Andre; Totapally, Balagangadhar R.
Abstract : BACKGROUND: The purpose of this study was to explore the epidemiology and outcomes of hospitalized children with a diagnosis of accidental hypothermia. METHODS: The 2012 Kids' Inpatient Database, detailing discharge diagnoses in children admitted to US hospitals, was analyzed using International Classification of Diseases, Ninth Revision, Clinical Modification codes to filter out relevant patients. Children ages 1 month to 17 years were included in the analysis. Demographic and outcome variables in the hypothermia group were compared with the rest of the patients. In a separate analysis, children with hypothermia were matched 1:1 using a correlative propensity score using sex, age, hospital region, income quartiles, race, ventilation status, coagulopathy, drowning, and All Patient Refined Diagnosis Related Groups severity score and their outcomes were compared with controls. The sample data were weighted to get a national estimate. RESULTS: Accidental hypothermia was present in 1, 028 cases out of 1, 915, 435 discharges. Children with hypothermia were more likely to be males (54.7% vs. 50.9%; p < 0.05) and infants (32.6% vs. 17.5%); they were less likely to be teens (30% vs. 37.8%). Children with hypothermia were more likely to be admitted in the Southern region (48.3% vs. 38.4%; p < 0.05) and have a higher mortality rate compared to all other discharges (8.5% vs. 0.3%; p < 0.05) or when compared with the matched controls (8.9% vs. 4.4%). CONCLUSIONS: The diagnosis of accidental hypothermia significantly increased mortality in hospitalized children. Interestingly, accidental hypothermia was more common in Southern states compared to the other areas of the United States. LEVEL OF EVIDENCE: Prognostic/epidemiological study, level III.